Prevalence of shunt dependence and clinical outcome in patients with massive intraventricular haemorrhage treated via endoscopic washout versus external ventricular drainage - A/L Johnson, Jason Raj (2015)
Methods: We have treated 16 patients with massive IVH with endoscopic washout as per study protocol to address all the undesired sequelae caused by IVH. 23 patients of the same disease were treated via external ventricular drainage. Results: All patients treated with endoscopic washout recovered well and only 3 patients required further shunt surgery at 3 months duration. There is significant difference in the shunt dependency between both control and intervention group (p-0.004). The duration of weaning of the external ventricular catheter is significantly shorter in the endoscopic washout group (p-0.007) and the Graeb score reduction is significantly more in the endoscopic washout group (p-0.001). Conclusions: Good outcomes obtained from endoscopic washout for massive intraventricular haemorrhage may be related to early removal of hematomas, creation of new cerebrospinal diversion pathway, coupled with early weaning from external ventricular drain and ventilator. The use of neuroendoscopy in patients with massive IVH has significantly reduced the drainage dependency and therefore all shunt related complications are also avoided.